1968
DOI: 10.1029/ja073i021p06783
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and results of low-frequency CW Rocket Propagation Experiments in theDregion

Abstract: Two low‐frequency (163 kHz), continuous‐wave rocket propagation experiments were performed at Fort Churchill, Manitoba, Canada, in the summer of 1963. The analysis and results of these experiments in terms of electron density profiles are presented. The results are compared with those obtained from an AC conductivity probe flown on the same rockets and, in one instance, with Langmuir probe measurements made on another rocket at about the same time during the solar eclipse of July 20, 1963, at Fort Churchill. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…At least three different rocket techniques have been used to measure electron density profiles. One technique, developed by Hall andFooks [1965, 1967] and Seliga [1966Seliga [ , 1968, utilized LF radio wave propagation from a ground transmitter to a rocket-borne receiver. In this method, the signal amplitude or scalar field o.f the LF wave was measured at the rocket.…”
mentioning
confidence: 99%
“…At least three different rocket techniques have been used to measure electron density profiles. One technique, developed by Hall andFooks [1965, 1967] and Seliga [1966Seliga [ , 1968, utilized LF radio wave propagation from a ground transmitter to a rocket-borne receiver. In this method, the signal amplitude or scalar field o.f the LF wave was measured at the rocket.…”
mentioning
confidence: 99%
“…The total solar eclipse began at 16 Fig. 1 shows the totality path of the solar eclipse, as well as the great circle paths for the experiment configuration between NML and the VLF receivers in CO and UT (denoted as the NML-CO and NML-UT paths hereafter).…”
Section: Methodsmentioning
confidence: 99%
“…Using rocket experiments, Sears et al [13] directly investigated the variation of electron density in the D-region ionosphere during the 1966 solar eclipse in South America. However, previous studies of the solar eclipse using rocket sounding mostly measured the electron density at altitudes above ∼70 km [16]- [19] and the electron concentration below this altitude remains poorly investigated. More recently, a detailed modeling study of the solar eclipse in Europe on August 11, 1999 [14] revealed that the amplitude of VLF signals was usually enhanced for relatively short propagation paths (<2000 km) and diminished for relatively long propagation paths (>10000 km).…”
Section: Introductionmentioning
confidence: 99%
“…Further details on ionospheric layer profiling using rocket beacon signals are described by Bernhardt et al. (1993), Evans (1977), Friedman (1959), Jackson (1954), Maeda (1970), Seliga, 1968, and Smith and Gilchrest (1984).…”
Section: Introductionmentioning
confidence: 99%